The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1523/jneurosci.19-11-04337.1999
|View full text |Cite
|
Sign up to set email alerts
|

The Mitogen-Activated Protein Kinase Cascade Couples PKA and PKC to cAMP Response Element Binding Protein Phosphorylation in Area CA1 of Hippocampus

Abstract: Activation of the mitogen-activated protein kinase (MAPK) cascade recently was discovered to play an important role in synaptic plasticity in area CA1 of rat hippocampus. However, the upstream mechanisms regulating MAPK activity and the downstream effectors of MAPK in the hippocampus are uncharacterized. In the present studies we observed that hippocampal MAPK activation is regulated by both the PKA and PKC systems; moreover, we found that a wide variety of neuromodulatory neurotransmitter receptors (metabotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
420
1
6

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 504 publications
(446 citation statements)
references
References 51 publications
(57 reference statements)
19
420
1
6
Order By: Relevance
“…Upstream of pCREB, N 2 O and xenon exhibit divergent effects on PKC signalling; preconditioning with xenon upregulates PKC activity (Weber et al, 2005), while N 2 O has been shown to inhibit PKC activity (Fukura et al, 2000). PKC is able to phosphorylate CREB (Roberson et al, 1999); together with its transcriptional coactivator, CBP, pCREB upregulates the expression of a number of genes, including Bcl-2 and BDNF (Wilson et al, 1996;Tao et al, 1998) and their corresponding proteins. In our study, we did show upregulation of pCREB and Bcl-2 as well as BDNF and this pathway may contribute to the mechanism for the preconditioning effect exerted by xenon (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upstream of pCREB, N 2 O and xenon exhibit divergent effects on PKC signalling; preconditioning with xenon upregulates PKC activity (Weber et al, 2005), while N 2 O has been shown to inhibit PKC activity (Fukura et al, 2000). PKC is able to phosphorylate CREB (Roberson et al, 1999); together with its transcriptional coactivator, CBP, pCREB upregulates the expression of a number of genes, including Bcl-2 and BDNF (Wilson et al, 1996;Tao et al, 1998) and their corresponding proteins. In our study, we did show upregulation of pCREB and Bcl-2 as well as BDNF and this pathway may contribute to the mechanism for the preconditioning effect exerted by xenon (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…(Weber et al, 2005). Consequently, cAMP-response element-binding protein (CREB) is transformed into the phospho-CREB (pCREB) form (Roberson et al, 1999). The CREB and CREB-binding protein (CBP) interaction can then induce transcription of a battery of CREB-dependent survival genes.…”
Section: Discussionmentioning
confidence: 99%
“…ERK can be regulated by the PKA or PKC cascade (Roberson et al, 1999) downstream of 5-HT 1A or 5-HT 2A/C receptors. However, application of the low concentration of 5-HT 1A or 5-HT 2A/C agonist (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 4A and 4B, the reducing effect of 8-OH-DPAT (with NMDA present) on spikes was prevented in cells dialyzed with the PKA inhibitor PKI 6-22 (20 μM, -6.9 ± 3.0%, n = 5, Figure 4E), while it was not affected by the PKC inhibitor calphostin (1 μM, Figure 4C, 30.6 ± 3.5%, n = 4, Figure 4E), suggesting the specific involvement of PKA. Since inhibition of PKA could result in the inhibition of ERK via the Rap1/B-Raf/MEK cascade (Vossler et al, 1997;Roberson et al, 1999), we also examined the involvement of ERK in the 5-HT 1A regulation of AP firing. As shown in Figure 4D, injecting cells with the ERK kinase inhibitor U0126 (20 μM) prevented 8-OH-DPAT from reducing the firing rate (-5.0 ± 2.3%, n = 12, Figure 4E).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation